Learning/teaching philosophy in sign language as a cultural issue - DE FÁTIMA SÁ CORREIA, MARIA; Coelho, Orquídea; Magalhães, António; Benvenuto, Andrea (Journal of Education Culture and Society, 2020)
This paper is about the process of learning/teaching philosophy in a class of deaf stu-dents. It starts with a presentation of Portuguese Sign Language that, as with other sign lan-guages, is recognized as a language on equal terms with vocal languages. However, in spite of the recognition of that identity, sign languages have specifi city related to the quadrimodal way of their production, and iconicity is an exclusive quality. Next, it will be argued that according to linguistic relativism - even in its weak version - language is a mould of thought. The idea of Philosophy is then discussed as an area of knowledge in which the author and the language of its production are always present.Finally, it is argued that learning/teaching Philosophy in Sign Language in a class of deaf students is linked to deaf culture and it is not merely a way of overcoming diffi culties with the spoken language